Can Rubrics Facilitate Student Assessment in Problem Based Learning? - K. Ramnarayan2, H. Shyamala Hande1* and (Recent Research in Science and Technology, 2011)
<p class="MsoNormal" style="margin: 0in 0in 0pt; text-align: justify; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 3.5in 280.0pt 308.0pt 336.0pt; mso-pagination: none; mso-layout-grid-align: none;">The study describes the need to have a systematic, at the same time Ã¢â‚¬Å“fit for purposeÃ¢â‚¬Â rubric that will enable faculty/tutors to assess studentsÃ¢â‚¬â„¢ performance constructively and reliably in Problem-Based Learning (PBL). A four-level assessment rubric having ten- performance objects with descriptors, five each for the two sessions of PBL was developed. Faculty and student feedback in the form of questionnaire was taken to evaluate the process. 81% of faculty reported that the rubric was useful in assessing students and 91% of students felt that it was Ã¢â‚¬Å“very importantÃ¢â‚¬Â that faculty should use the rubric as it reflected authenticity in assesment.